The Relationship Between Sleep Quality and Anxiety Levels in Pregnant Women After Performing Prenatal Yoga - Sri Anggararini Parwatiningsih; M. Nur Dewi Kartikasari; Indhun Dyah Susanti; Septiana Juwita (Jurnal Kebidanan, 2026)
Prenatal yoga is a modification of classical yoga practice in which the movements have been specifically adapted to the conditions and needs of pregnant women. It has potential benefits for overcoming sleep disturbances and is effective in reducing anxiety, stress, and depressive symptoms in pregnant women. This study aimed to analyze the relationship between sleep quality and anxiety levels among pregnant women after participating in prenatal yoga. This study employed an analytical method with a correlational design using a cross-sectional approach. Purposive sampling was used to obtain 33 respondents. The intervention provided was prenatal yoga. The research instruments included the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality and the Hamilton Anxiety Scale to measure anxiety levels. Data were analyzed using the Spearman rank correlation test. The results showed that 84.85% of pregnant women had good sleep quality. Most respondents experienced mild anxiety (39.39%), followed by moderate anxiety (27.27%) and severe anxiety (27.27%), while 6.06% experienced very severe anxiety. The Spearman rank correlation coefficient indicated that sleep quality was not significantly associated with anxiety levels (ρ = -0.023; p-value = 0.897). In conclusion, prenatal yoga may be associated with improved sleep quality and lower anxiety levels. However, no significant relationship was found between sleep quality and anxiety levels in this study.